Combined modality therapy for exsudative form of age-related macular degeneration - М. V. Budzinskaya; I. V. Gurova; I. V. Schegoleva; V. B. Loschenov; S. А. Shevchik; S. G. Kuzjmin; G. N. Vorogtsov (Biomedical Photonics)
Treatment outcomes in patients with age-related vascular degeneration due to formation of subretinal neovascular membrane (SNM) of two groups: photodynamic therapy (PDT) with Photosens alone (18 patients) and in combination with anti-VEGF therapy with Lucentis (20 patients). For both groups Photosens was administrated i.v. in single dose of 0.05 mg/kg. The irradiation was performed on the 3rd day (the wave length 675 nm, light dose 120 J/cm2, total light dose did not exceed 500 J/cm2). The number of sessions accounted for 3 to 5 per week according to clinical manifestation of SNM. Patients with multimodality treatment had intravitreal administration of Lucensis in dose 0.05 ml (0.5 mg). The study showed that combination of PDT and anti-VEGF therapy improved vision better and with more stable effect then PDT alone. Thus vision improvement and decrease of SNM activity occurred in 50% of patients with PDT alone and in 60% of patients with multimodality treatment. For 2-year follow-up in the group of PDT alone the vision gradient gradually decreased compared with baseline vision (from 0.11 to 0.06), in the group of multimodality treatment gradual increase of vision gradient was noticed (from 0.03 to 0.155). The superior efficiency of PDT combined with anti-VEGF therapy compared with PDT alone in patients with age-related vascular degeneration was confirmed by study of vision, fundus angiography and average thickness of retina in foveola in both groups.